PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PENBENTUKAN NILAI MORAL PADA PESERTA DIDIK DI SMA IBRAHIMY SUKOREJO SITUBONDO - Baihaki, Imam; Solechan (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research discusses the role of Islamic education teachers in forming moral values ​​in students. In the educational context, teachers not only function as transmitters of material, but also as role models and mentors who have a big responsibility in developing student character. PAI teachers also have a multifunctional role as educators, models or role models, facilitators, motivators, evaluators, teachers, mentors, and trainer. They must create a dynamic-constructive learning environment, analyze the weaknesses of the material and students, and provide moral encouragement for students to develop holistically. Through an Islamic education approach, teachers can apply effective methods to instill moral values, such as honesty, responsibility and mutual respect. This research uses qualitative methods with interviews and observations. The results show that positive interactions between teachers and students, as well as the application of Islamic values ​​in learning activities, contribute significantly to strengthening students' morale. It was also found that the involvement of parents and the community in the educational process increases the effectiveness of the formation of moral values. The conclusions of this research emphasize the important role of teachers in creating a generation that is not only academically intelligent, but also moral and ethical.